2019
DOI: 10.1016/j.ridd.2019.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Student–teacher relationships of children with autism spectrum disorder: Distinct contributions of language domains

Abstract: Background and Aims-High quality student-teacher relationships (STR) are important for children's academic and social development. We explore how individual child language domains (semantics, syntax, pragmatics), teacher years of experience, and classroom placement (general or special education) relate to STR quality for children with autism spectrum disorder (ASD) across the school year. Methods and Procedures-191 children with ASD (M age = 5.6 years) completed a standardized language assessment and their tea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…The pathways between children's internalizing symptoms and their social adjustment over time may be facilitated or disrupted by aspects of their school experience. Namely, their classroom placement (general education vs. special education) may impact these pathways, aligned with research showing that children's student-teacher relationships and peer relationships often differ between classroom types (Feldman et al, 2019). Likewise, teachers who have autism-specific training may be equipped to alter these pathways by supporting children's social and emotional well-being even in the context of early social or internalizing difficulties.…”
Section: Classroom Type and Teacher Training As Moderatorsmentioning
confidence: 78%
“…The pathways between children's internalizing symptoms and their social adjustment over time may be facilitated or disrupted by aspects of their school experience. Namely, their classroom placement (general education vs. special education) may impact these pathways, aligned with research showing that children's student-teacher relationships and peer relationships often differ between classroom types (Feldman et al, 2019). Likewise, teachers who have autism-specific training may be equipped to alter these pathways by supporting children's social and emotional well-being even in the context of early social or internalizing difficulties.…”
Section: Classroom Type and Teacher Training As Moderatorsmentioning
confidence: 78%
“…Evidently, children need an emotion-related receptive vocabulary to be able to reflect upon their own and others' emotions in a sophisticated way (Pons et al, 2006), and their expressive language skills enable them to engage in more mental state talk that further enhances their EU (Taumoepeau & Ruffman, 2008). Furthermore, LAUGEN, KÅRSTAD, REINFJELL, AND WICHSTRØM children with better language skills are also more likely to obtain skills required to develop high-quality relationships with parents, teachers, and peers (Chow et al, 2022;Davis & Qi, 2020;Feldman et al, 2019). Consequently, with verbal ability being associated with both relationship quality and the level of EU, there is a risk of spurious results reflecting verbal ability rather than relationship quality.…”
Section: Verbal Abilitymentioning
confidence: 99%
“…The few existing studies that have addressed TSR in ASD students have revealed that this relationship is characterized by less closeness and more conflict compared to the relationship between teachers and students with TD (Blacher et al, 2014;Caplan et al, 2016;Feldman et al, 2019;Prino et al, 2016;Roorda et al, 2021). The more challenging relationship between teachers and students with Autism Spectrum Disorder (ASD) may stem from the students' difficulties in social interactions, such as understanding social cues, maintaining conversations (Davis & Crompton, 2021), and interpreting emotional expressions .…”
Section: Introductionmentioning
confidence: 99%
“…These contradictory results (regarding whether students with ASD report a worse or better relationship with their teachers compared to their peers with TD) could also be explained by the different reports used. Evidence that the relationship between teachers and students with ASD is characterized by less closeness and more conflict has been constructed from teacher reports, not from student reports (Blacher et al, 2014;Caplan et al, 2016;Feldman et al, 2019;Prino et al, 2016;Roorda et al, 2021). The only study that has found positive reports of TSR with ASD did so precisely from the report of students .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation